(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the origins of the area of speech culture, summarizes the views of Uzbek and Russian scientists on the development of this area. The article discusses the issues that need to be resolved from the point of view of the norms of the literary language and how to comply with these norms.